2002
DOI: 10.1021/ja011041d
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal P450-Catalyzed N-Dealkylation of N,N-Dialkylanilines:  Evidence for a Cα−H Abstraction Mechanism

Abstract: The early proposal that P450-catalyzed N-dealkylation of N,N-dialkylamines proceeds through a single-electron-transfer (SET) mechanism was later challenged in favor of the C(alpha)-H abstraction mechanism. In the present study, a series of N-alkyl-N-cyclopropyl-p-chloroaniline probes have been used to examine whether the P450-catalyzed N-dealkylations proceed through a C(alpha)-H abstraction and/or a SET mechanism, using phenobarbital-induced rat liver microsomal P450 enzymes as a model system. While the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 32 publications
(15 reference statements)
1
38
0
Order By: Relevance
“…11,49,51 The current view, which is supported by large intramolecular isotope effects for amide N-dealkylations (> 13), DFT studies and the lack of ring opening products with N-cyclopropyl substrates, is that a HAT mechanism occurs for Ndealkylation. [52][53][54][55][56] DFT calculations on selected para-substituted N,N-dimethylanilines showed that the radical cation arising from the first single electron transfer on the SET pathway was significantly higher in energy than its radical counterpart on the HAT pathway 57 and that dealkylation products can arise from either of the two spin-states of Cpd I depending on the nature of the substrate's substituent. 51,57,58 Some unusual major metabolites were observed during this work, including the isolable, stable cyclic hemiacetal from 3,4-diethylenedioxy benzoic acid.…”
Section: Two Main Mechanistic Pathways Have Been Proposed For Heteroamentioning
confidence: 99%
“…11,49,51 The current view, which is supported by large intramolecular isotope effects for amide N-dealkylations (> 13), DFT studies and the lack of ring opening products with N-cyclopropyl substrates, is that a HAT mechanism occurs for Ndealkylation. [52][53][54][55][56] DFT calculations on selected para-substituted N,N-dimethylanilines showed that the radical cation arising from the first single electron transfer on the SET pathway was significantly higher in energy than its radical counterpart on the HAT pathway 57 and that dealkylation products can arise from either of the two spin-states of Cpd I depending on the nature of the substrate's substituent. 51,57,58 Some unusual major metabolites were observed during this work, including the isolable, stable cyclic hemiacetal from 3,4-diethylenedioxy benzoic acid.…”
Section: Two Main Mechanistic Pathways Have Been Proposed For Heteroamentioning
confidence: 99%
“…93,94,95 However, evidence has gradually been gathered against this hypothesis, and hydrogen abstraction pathways are now privileged. 96,97,98,99,100,101 It is also worth mentioning that the ring-cleavage of aminocyclopropanes by single-electron oxidation has been used to design a cyclopropylamine-derived nucleobase able to terminate DNA-mediated hole transport. 102 Several of the synthetic methodologies developed on the basis of single electron oxidation involve trapping of the ring-opened distonic radical cation 41 by an alkene, an alkyne or by triplet oxygen.…”
Section: Electrophilic Halogenationmentioning
confidence: 99%
“…5 The salient outcomes of this study include the following: (1) replacement of the C(1)-cyclopropyl proton with a methyl group shifts the product composition from a mixture of the N-dealkylated and Ndecyclopropylated metabolites to the N-dealkylated metabolites † AstraZeneca R&D Mölndal. ‡ Virginia Tech.…”
Section: Introductionmentioning
confidence: 99%